77 Developing and Testing An Education-Career Pathway in Healthcare for Older People (ECHO) to Promote Retention in Early-Career Gerontological Nurses. (6th February 2020) - Naughton, C; Ezhova, I; Hayes, N; Fitzpatrick, J
Abstract: Background: The NHS Long Term Plan (2019) sets specific targets for multidisciplinary services for frail older people over the next ten years. Delivery and sustainability is crucially dependant on the capability and capacity of gerontological nursing. High cost cities such as London experience high staff vacancy rates in acute care older adult services. Aim: The study took a regional approach, working with NHS Trusts to develop a multicomponent intervention to increase retention and competencies of early career nurses working in gerontological services. The study examined the acceptability and feasibility of the intervention and tested a quasi-experiential evaluation design. Ethical approval was obtained from the University Ethics committee. Methods: A co-design approach with stakeholders, early career nurses, educationalists and nurse managers, produced a multicomponent intervention: education module (masters level), gerontological competency booklet, external clinical learning opportunities, career coaching and mentorship delivered over a six-month period. The evaluation involved a mix-methods pre-post survey and focus group interviews. Results: Twenty-nine early career nurses were recruited from five Trusts. The multicomponent intervention was well received, but there were difficulties facilitating external learning opportunities and providing career mentors. The primary outcome was intention to remain in gerontological nursing (measured using a point Likert scale). Pre-post the intervention this remained high (mean score 6 IQR 5-7), p=0.78. There was a significant increase in gerontological knowledge: at baseline the median score was 87 (IQR 81-102) compared to 107 (IQR 98-112) post-intervention, p=0.006. In focus groups participants identified three main mechanism of action for ECHO: building gerontological knowledge and skills; professional identity as older adult nurse; and networking to broaden horizons. Conclusions: The study has demonstrated the potential of Trusts to work collaboratively with education providers to deliver a model of career-education pathway that may help attract and retain early career nurses to work in gerontology.